Indian perspectives in the works of Albert Roussel and Maurice Delage - KARACSONY, Noemi; RUCSANDA, Mădălina Dana (Universitatea Transilvania Brasov, 2022)
French composers Albert Roussel and Maurice Delage were strongly influenced by Classical Indian music, the evocation of this exotic world offering them the opportunity to devise innovative musical languages. The present paper strives to reveal the manner in which both Roussel and Delage employ in their works modal constructions, inspired by Indian ragas, vocal and instrumental timbres that can be associated by the Western listener with the sound of Indian music, at the same time incorporating in their works rhythmic patterns and sound effects specific for Indian music. The orientalism and exoticism in the works of these two composers reflect their desire to obtain a certain purity of the artistic expression, while the direct contact with the music of India and that of other regions in Asia, visited by Roussel and Delage, contributed in a great deal to their transcending of the philosophical, social, and even musical barriers and limitations, offering them the freedom to turn to new means of musical expression in their works.
Keywords: orientalism; exoticism; Albert Roussel; Maurice Delage; influences